O Meio Empreendedor Promovendo Inovação A Geração de Capital Social no Porto Digital - Fernando Gomes de Paiva Júnior (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2016)
The relational inputs are known in the business environment by knowledge, information, trust, ideas,loyalty and commitment, together they constitute an intangible good, the social capital. The enterpriseenvironment highlights the interfaces of the territorial and socio-cultural dimensions on the local ambit.This field still have deficiencies, demanding bigger attention, by the ones who interact on the samearea seeking the same goals and by research scientists fir achieving progress and sustainability ofthe institutions. The study aims to describe how the capital social production works, also its creatinginnovation effects, on this empirical Porto Digital case. This is a qualitative research with descriptivebibliographical, documentary survey and analysis reports from the Porto Digital leaders interviews.The data analysis was based on the interviews, comparing the answers with the theoreical and docu-mentary analysis. The results reveals that there is a suitable environment for social and technologicaldevelopment. As well as relevant actions to posture and behavior arising from the relational aspectof the actors immersed in the network. The components of interpersonal relationships are essentialto the creation of innovative environment and its progressive sustainability.